FATIGUE LIFE ESTIMATION OF DIFFERENT WELDING ZONES OF OXY ACETYLENE WELDED ALUMINUM ALLOY (AA 5052-H32) - Mudaserullah, M.; Pasha, R. A.; Rahman, R. A.; Asghar, W. (The Nucleus, 2013)
Fatigue life of aluminum alloys are reviewed mainly on the basis of experimental results. Fatigue strength and failure history of the representative AA5052-H32 are summarized with respect to surface temperature effects during the welding process. In oxy acetylene welding three different zones named as welded zone (WZ), heat affected zone (HAZ) and base metal (BM) are formed having totally varying properties depending on their specific grain structure. Fatigue life and hardness of these different zones are determined in three successive phases of experiments. It is viewed that the grains are shifted from large rough round to elongated oval shaped from WZ to HAZ and relatively small and fine in BM respectively. Depending on grain configuration the fatigue strength increases from WZ to BM due to concentration of grain boundaries, a hindrance in fatigue crack propagation.